Degenerated vision, altered lipid metabolism, and expanded chemoreceptor repertoires enable Lindaspio polybranchiata to thrive in deep-sea cold seeps - Yujie Yan; Inge Seim; Yang Guo; Xupeng Chi; Zhaoshan Zhong; Dantong Wang; Mengna Li; Haining Wang; Huan Zhang; Minxiao Wang; Chaolun Li (BMC Biology)
Abstract Background Lindaspio polybranchiata, a member of the Spionidae family, has been reported at the Lingshui Cold Seep, where it formed a dense population around this nascent methane vent. We sequenced and assembled the genome of L. polybranchiata and performed comparative genomic analyses to investigate the genetic basis of adaptation to the deep sea. Supporting this, transcriptomic and fatty acid data further corroborate our findings. Results We report the first genome of a deep-sea spionid, L. polybranchiata. Over long-term adaptive evolution, genes associated with vision and biological rhythmicity were lost, which may indirectly benefit oligotrophy by eliminating energetically costly processes. Compared to its shallow-sea relatives, L. polybranchiata has a significantly higher proportion of polyunsaturated fatty acids (PUFAs) and expanded gene families involved in the biosynthesis of unsaturated fatty acids and chromatin stabilization, possibly in response to high hydrostatic pressure. Additionally, L. polybranchiata has broad digestive scope, allowing it to fully utilize the limited food resources in the deep sea to sustain a large population. As a pioneer species, L. polybranchiata has an expanded repertoire of genes encoding potential chemoreceptor proteins, including ionotropic receptors (IRs) and gustatory receptor-like receptors (GRLs). These proteins, characterized by their conserved 3D structures, may enhance the organism’s ability to detect chemical cues in chemosynthetic ecosystems, facilitating rapid settlement in suitable environments. Conclusions Our results shed light on the adaptation of Lindaspio to the darkness, high hydrostatic pressure, and food deprivation in the deep sea, providing insights into the molecular basis for L. polybranchiata becoming a pioneer species.